1) 6x+7y=-9
-4x-5y=5

-5y=4x+5
y=-4/5(x)-1

6x+7y=-9
6x+7(-4x/5-1)=-9
6x-28x/5-7=-9
2/5(x)=-2
multiply both sides by 5
2x=-10
x=-5

6x+7y=-9
-30+7y=-9
7y=21
Y=3

\( \begin{cases} 6x+7y=-9 \\ -4x-5y=5 \end{cases}\\ \\\begin{cases} 6x =-7y-9 /:6\\ -4x-5y=5 \end{cases}\\ \\\begin{cases} x =-\frac{7}{6}y-\frac{9}{6}\\ -4x-5y=5 \end{cases}\\ \\\begin{cases} x =-\frac{7}{6}y-\frac{3}{2}\\ -4*(-\frac{7}{6}y-\frac{3}{2})-5y=5 \end{cases} \)

\( \begin{cases} x =-\frac{7}{6}y-\frac{3}{2}\\ \frac{14}{3}y+6-5y=5 \end{cases} \\ \\\begin{cases} x =-\frac{7}{6}y-\frac{3}{2}\\ \frac{14}{3}y-\frac{15}{3}y=5-6 \end{cases} \\ \\\begin{cases} x =-\frac{7}{6}y-\frac{3}{2}\\ -\frac{1}{3}y=-1/(-3) \end{cases} \)

\( \begin{cases} x =-\frac{7}{6}*3-\frac{3}{2}\\ y=3 \end{cases} \\ \\\begin{cases} x =-\frac{7}{2}-\frac{3}{2}\\ y=3 \end{cases}\\ \\\begin{cases} x =-\frac{10}{2}\\ y=3 \end{cases} \\ \\\begin{cases} x =-5\\ y=3 \end{cases} \)



RELATED: